The effects of anaerobic training in serum lipids and arachidonic acid metabolites - Kipreos, G.; Tripolitsiotis, A.; Stergioulas, A. (Biology of Exercise, 2010)
Coronary arteries are subjected daily in high shear stress and manifest atherosclerosis very early in life in comparison to other arteries in the human body. Some factors that are implicated in the evolution and progress of this process are the concentration of lipids and arachidonic acid metabolites, such prostacyclin and thromboxane. It has been reported that those who participate in aerobic activities such as walking, cycling, jogging or brisk walking might have normal values of the mentioned chemical substances. On the other hand, it is reported that the effects of anaerobic and strength activities has negative effects on the vascular endothelium, which is essential for the maintenance of hemostatic balance and the local regulation of vascular tone. Therefore, even although extensive research has been conducted in this field, there are crucial gaps in our knowledge. Consequently, the purpose of this brief review is to describe what is known about the effects of anaerobic activities in which the competitive athletes have participated on the following blood parameters: Total cholesterol, triglycerides, high density lipoprotein cholesterol (HDL - C), low density lipoproteins cholesterol (LDL - C), prostacyclin & thromboxane.